Microbial and quality attributes of thermally processed chili shrimp paste - Sobhi, Babak; Mohd Adzahan, Noranizan; Abdul Karim, Muhammad Shahrim; Abdul Rahman, Russly; Bakar, Jamilah; Ghazali, Zulkafli (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Chili shrimp paste (CSP) is a favorite condiment in Southeast Asia. Microbial spoilage makes CSP unsuitable for consumption within several days. Thermal treatment was applied to produce microbiologically safe CSP. The effect of heating process on physicochemical and sensorial properties of CSP was studied. Heating at the optimum condition (21.6 min, 80 °C) has been shown effective and reliable in controlling microorganisms in CSP. Complete inactivation of peroxidase activities could not be accomplished at the optimal point, and significant reduction of the total phenolic and capsaicinoids contents was observed. Sensorial evaluation indicated that thermally processed CSP was less preferred by panelists when compared to freshly prepared samples of dry weight respectively.